Determinan Kinerja Karyawan di Era Digital : Analisis Integrasi Faktor Transformasi Digital, Pemberdayaan Psikologis, dan Motivasi Kerja - Restya, Galuh Putri; Hendra Achmadi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
The purpose of this study is to analyze the influence of OCB and work motivation, both partially and simultaneously, on the performance of KONI West Java employees. The research method used was a quantitative approach with a survey technique. Data collection was conducted by distributing questionnaires to KONI West Java employees as respondents. Data analysis used multiple linear regression to determine the magnitude of the influence of each variable. The results showed that OCB had a positive and significant effect on employee performance. Work motivation was also shown to have a positive and significant effect on performance. Simultaneously, OCB and work motivation made a significant contribution in explaining employee performance variables. The conclusion of this study is that increasing OCB and strengthening work motivation are crucial in efforts to improve employee performance within the KONI West Java environment. These findings can serve as a basis for management in designing strategies to improve work quality and organizational productivity.   Keywords: Organizational Citizenship Behavior, Work Motivation, Employee Performance